Strategi Mengatasi Hate Speech Di Media Sosial Dalam Perspektif Islam - Fatimah Az Zahra .; Asyiri Abghiya R; Nurti Budiyanti; Nabila Azzahra; Muhammad Ikhsan Ag (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
Social media is a tool for easily conveying one's opinion, thus it often happens that someone's opinion is conveyed through social media which crosses reasonable boundaries and is based on hatred so that restrictions on freedom of expression through social media are necessary, in this case as we know that al -The Qur'an discusses six ways to communicate, for example the first is Qaulan Karimah, the second is Qaulan Maysura, the third is Qaulan Balighan, the fourth is Qaulan Layyinan, the fifth is Qaulan Sadidan, and finally is Qaulan Ma'rufan. This writer uses a qualitative descriptive method by collecting data from literature sources, such as from journal references (national & international), articles, books, the Koran and hadith which discuss strategies for dealing with hate speech on social media. Understanding of the six ways to communicate helps to overcome problems in social media. Keywords: Social media, freedom of expression, hate speech, how to communicate